In search of an international multidimensional action plan for second victim support: a narrative review - Deborah Seys; Massimiliano Panella; Sophia Russotto; Reinhard Strametz; José Joaquín Mira; Astrid Van Wilder; Lode Godderis; Kris Vanhaecht (BMC, 2023)
Abstract Background Insights around second victims (SV) and patient safety has been growing over time. An overview of the available evidence is lacking. This review aims to describe (i) the impact a patient safety incident can have and (ii) how healthcare professionals can be supported in the aftermath of a patient safety incident. Methods A literature search in Medline, EMBASE and CINAHL was performed between 1 and 2010 and 26 November 2020 with studies on SV as inclusion criteria. To be included in this review the studies must include healthcare professionals involved in the aftermath of a patient safety incident. Results In total 104 studies were included. SVs can suffer from both psychosocial (negative and positive), professional and physical reactions. Support can be provided at five levels. The first level is prevention (on individual and organizational level) referring to measures taken before a patient safety incident happens. The other four levels focus on providing support in the aftermath of a patient safety incident, such as self-care of individuals and/or team, support by peers and triage, structured support by an expert in the field (professional support) and structured clinical support. Conclusion The impact of a patient safety incident on healthcare professionals is broad and diverse. Support programs should be organized at five levels, starting with preventive actions followed by self-care, support by peers, structured professional support and clinical support. This multilevel approach can now be translated in different countries, networks and organizations based on their own culture, support history, structure and legal context. Next to this, they should also include the stage of recovery in which the healthcare professional is located in.